Understanding the pathogenesis of infertility in endometriosis - literature review - Szymańska, Wiktoria Maria; Wójcik, Julia; Kantor, Karolina Kinga; Plewniok, Julia; Partyka, Maria; Pamuła, Kacper Wojciech; Janeczek, Maksymilian; Cholewa, Marcin; Jaglarz, Karolina; Kuca, Maciej (Quality in Sport, 2024)
Introduction and objective Endometriosis is a complex systemic condition characterized by the growth of functional endometrial tissue outside the uterine cavity, affecting 10-15% of women of reproductive age. Up to 50% of these women face infertility challenges. Although there is a scientifically established connection between endometriosis and infertility, the underlying mechanisms remain not fully understood. Review methods The PubMed database was searched using phrases related to the topic of endometriosis-associated infertility. The search included original research articles, review papers, and guidelines, including the Polish guideline on managing women with endometriosis. Ultimately, 25 relevant sources presenting the latest knowledge were selected. Abbreviated description of the state of knowledge The pathogenesis of infertility associated with endometriosis is complex and involves multiple factors. The most frequently cited contributors in the scientific literature include pain and dyspareunia, mechanical factors, reduced ovarian reserve, oxidative stress, changes in embryo and oocyte quality, impaired ovulation, and compromised endometrial receptivity. Summary Endometriosis affects a growing number of women worldwide, with nearly half experiencing infertility. The complexity and involvement of multiple organ systems make it difficult to pinpoint a single cause, posing a challenge for clinicians. Addressing these diverse factors is essential for improving fertility management in women with endometriosis.